Mirror, Mirror on the Wall, What is the Best Topology of Them All? - Taufer, Michela (Communications of the ACM, 2024)
The article offers an introduction and overview to another article in the issue on the topic of how large-scale computers should be specifically designed to handle artificial intelligence and machine learning tasks. Topics include different types of parallelism in computing operations and topological considerations.